1997
DOI: 10.1038/bjc.1997.553
|View full text |Cite
|
Sign up to set email alerts
|

Use of power Doppler ultrasound-guided biopsies to locate regions of tumour hypoxia

Abstract: Summary The purpose of this study was to determine whether power Doppler ultrasound techniques could be used to direct biopsies into tumour regions with relatively low red blood cell flux, and therefore preferentially sample regions that were relatively hypoxic. Subcutaneous 9L glioma rat tumours were biopsied using power Doppler ultrasound guidance. Immunohistochemical detection of the 2-nitroimidazole EF5 was performed to determine the presence and level of hypoxia in the biopsy samples. Comparisons between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Neovascularization has been reported in many cancers as in prostate cancer. [14][15][16] In our study, cancer was detected in 36% by histopathological evaluation. In many studies performed with different imaging methods, the rate of cancer detection was reported to be 29-53%.…”
Section: Discussionsupporting
confidence: 46%
“…Neovascularization has been reported in many cancers as in prostate cancer. [14][15][16] In our study, cancer was detected in 36% by histopathological evaluation. In many studies performed with different imaging methods, the rate of cancer detection was reported to be 29-53%.…”
Section: Discussionsupporting
confidence: 46%
“…The finding of biopsies that demonstrate low Photofrin uptake in patients who have little EF5 binding in their disease brings to light the possibility that delivery of both agents may have been limited. However, extensive preclinical evaluation has established that under long incubation times, sufficient concentrations of hypoxia marker are delivered to label even low perfusion areas (31)(32)(33)(34)(35). Additionally, we always see EF5 binding adjacent to regions of necrosis.…”
Section: Discussionmentioning
confidence: 92%
“…It has been well-documented that cancers have neovascularity and can incite a vascular response. This has been reported with a variety of cancers as well as with prostate cancer [ 12 - 14 ]. In the present study, histopathological examination revealed a malignancy rate of 32.50%.…”
Section: Discussionmentioning
confidence: 75%